Reception of electronic evidence from Islamic perspective - Mustapa Sa‘di, Mursilalaili; Kamarudin, Abdul Rani; Ramlee Saad, Zulfakar (INSI Publications, 2015)
Islamic law of evidence acknowledges electronic evidence as documentary evidence or al-kitabah. It is in line with the Malaysian Law perspective since electronic evidence is one form of documentary evidence. It is stored and retrievable from electronic devices such as computer and smartphones to name a few. However, the fragile nature of electronic evidence, makes it prone to damage and alteration as well as destruction or when there is improper handling of such evidence. Since, it can easily be tempered or self-deteriorate, establishing authenticity, reliability and accuracy of electronic evidence are quite challenging to ensure such evidence is admissible and weighty. In order to ensure such evidence is admissible and carry the expected weightage, the parties must first prove the authenticity of such evidence, and subsequently on the contents‘ reliability and accuracy. Therefore, this article discusses what is documentary evidence under Islamic law known as al-kitabah and how the Islamic jurists treated it as a mode of proof it then discuss whether al-kitabah would include electronic evidence. Hence, this article explained the nature of electronic evidence as understood now based on several modern statutes and the requirement for is admissibility such as authentication of both the document as well as the content.